Financial Sector Reforms and Prospects for Financial Integration in Maghreb Countries - Sole, Juan (IMF Working Papers; Working Paper, 2007)
A healthy and dynamic financial sector is essential to achieving high and sustainable economic growth in the Maghreb region-Algeria, Libya, Mauritania, Morocco, and Tunisia. Financial integration within the Maghreb region will help deepen financial markets, increase their efficiency, and enhance the resilience of economies to shocks. It can also play a catalyst role for the global financial integration of the Maghreb region. This paper provides an overview of the financial systems, takes stock of the reform effort and highlights the challenges ahead, and examines the prospects for financial integration in the five Maghreb countries.